Accountants’ acceptance of accrual accounting systems in the public sector and its influence on motivation, satisfaction and performance - Eveana Mosuin; Tuan Zainun Tuan Mat; Erlane K. Ghani; Abdulaziz Alzeban; Ardi Gunardi (Management Science Letters, 2019)
This study examines the acceptance level of Accrual Accounting System (AAS) among the accountants in the public sector. Subsequently, this study examines whether the accountants’ acceptance level of AAS influences their motivation, job satisfaction and job performance. Using a cross sectional study via a questionnaire survey on 166 public sector accountants in the public sector, the study shows that the accountants accepted AAS. The study also shows that the acceptance of AAS among the accountants significantly influences their motivation, job satisfaction and job performance. Further analyses show that the accountants’ motivation to accept AAS significantly influences their job satisfaction and subsequently, job performance. The findings of this study indicates that acceptance of a technology could lead to positive attitude and ultimately, ensuring AAS implementation success in the public sector.